The Therapeutic Application of Hydrogen in Cancer: The Potential and Challenges - Khiji, Morteza N.; Arghidash, Faezeh; Tanha, Ghazaleh Khalili; Zadeh, Rasoul Hossein; Ghorbani, Elnaz; Khazaei, Majid; Hassanian, Seyed Mahdi; Gataa, Ibrahim Saeed; Lam, Alfred King-Yin; Giovannetti, Elisa; Ferns, Gordon A.; Nazari, Elham; et al. (Current Pharmaceutical Design, 2024)
Hydrogen therapy has emerged as a possible approach for both preventing and treating cancer. Cancers are often associated with oxidative stress and chronic inflammation. Hydrogen, with its unique physiological functions and characteristics, exhibits antioxidant, anti-inflammatory, and anti-apoptotic properties, making it an attractive candidate for cancer treatment. Through its ability to mitigate oxidative damage, modulate inflammatory responses, and sustain cellular viability, hydrogen demonstrates significant potential in preventing cancer recurrence and improving treatment outcomes. Preclinical studies have shown the efficacy of hydrogen therapy in several cancer types, highlighting its ability to enhance the effectiveness of conventional treatments while reducing associated side effects. Furthermore, hydrogen therapy has been found to be safe and well-tolerated in clinical settings. Nonetheless, additional investigations are necessary to improve a comprehensive understanding of the mechanisms underlying hydrogen's therapeutic potential and refine the administration and dosage protocols. However, further clinical trials are still needed to explore its safety profile and capacity. In aggregate, hydrogen therapy represents an innovative and promising treatment for several malignancies.
Keywords: therapeutic application